The chemistry of precipitation, throughfall and stemflow in two holm oak (Quercus ilex L.) forests under a contrasted pollution environment in NE Spain. (The Science of the total environment, 2003)
Atmospheric deposition was studied through measurements of bulk deposition, throughfall and stemflow at two sites of contrasted exposure to pollution in the Montseny mountains (Northeastern Spain). To explore the contribution of local or distant sources at both sites, concentration data and precipitation amounts (log transformed) for both bulk deposition and net throughfall were fitted by linear regression. These models indicated the more important contribution of washout scavenging processes and dry deposition at the pollution exposed site. This is relevant in the context of Mediterranean holm oak forests: up to now, most of the studies have been conducted in protected remote sites and were little representative of the fluxes in forests close to industrial activity, traffic, agriculture and residential areas.

Nitrogen deposition in Mediterranean forests. (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.

Carbon dioxide efflux and pCO 2 in soils of threeQuercus ilex montane forests (Biogeochemistry, 1995)
Soil CO2 efflux and pCO2 in the soil atmosphere were measured during one year at three montane sites of Mediterranean sclerophyllous forests in NE Spain. Two sites were located in the upper and lower slopes of a small catchment in the Prades mountains (mean precipitation 550 mm year-'), and a third site was located on a lower slope in the Montseny mountains (mean precipitation 900 mm year-'). The three sites were similar in bedrock and vegetation, but differed in soil characteristics and water availability. Seasonal variation of CO2 efflux and soil pCO2 were affected by soil temperature and, to a lesser extent, by soil moisture. Annual mean soil CO2 efflux (considered as soil respiration) was similar at Montseny and at the comparably located site at Prades (83 ± 18 S.E. vs. 75 4 9 mg CO2 m - 2 hour- , respectively), and was highest at the Prades upper slope site (122 ± 22 mg CO2 m -2 hour-l). Despite those relatively similar CO 2 effluxes, mean soil pCO2 was much higher at both Prades sites than at Montseny. Soil pCO2 always increased with depth at Prades while maxima pCO2 at Montseny were often at 20-30 cm depth. A model based on gas diffusion theory was able to explain why soil pCO2 was much higher at Prades than at Montseny, and to reproduce the shape of the vertical profile of pCO2 at the Prades soils. Nevertheless, the model failed to simulate the soil pCO2 maximum found at 20-30 cm depth at the Montseny site. Model simulations using a time-variable CO2 production rate suggested that pCO2 maxima at intermediate depth could be the result of a transient situation instead of an equilibrium one.

Modelling the long-term impacts of atmospheric pollution deposition and repeated forestry cycles on stream water chemistry for a holm oak forest in northeastern (Journal of Hydrology, 1995)
Estimates based on the MAGIC model of the long-term effects on stream water quality of forest management cycles as well as of atmospheric pollutant inputs for a holm oak catchment in northeastern Spain, show that despite high pollutant sulphur inputs as well as substantial base cation loss from the catchment owing to forest harvesting, stream water has not deteriorated in any major way. Acidification of the catchment will continue, to a limited degree, unless either sulphur deposition is reduced by more than 60% or forest harvesting schemes are terminated. The detrimental changes in water quality owing to acid deposition and forestry harvesting practice in other parts of Europe are not observed in this region, because of high base inputs from the atmosphere and high base cation weathering rates within the catchment.

Soilwater chemistry in a holm oak ( Quercus ilex) forest: inferences on biogeochemical processes for a montane-Mediterranean area (Journal of Hydrology, 1995)
Soil solution and free-flowing soilwater were sampled at various depths for 3 years in a plot of holm oak (Quercus ilex L.) in the Montseny mountains (NE Spain). The soil solution retained at -65M kPa in the mineral soil at depths of 20 and 40 cm had a different chemistry from that of throughflow under the humic layer (H-layer throughflow) and, to a lesser extent, from deep subsurface flow. The dominant mobile anion in the soil solution and the deep flow was SO:-, whereas in the H-layer, SOi- was overridden by alkalinity. H-Layer throughflow chemistry was extremely variable, in consequence of the large number of biogeochemical processes affecting it (e.g. rainfall chemistry, dry deposition, leaching from canopy and litter, decomposition), and of the quantity of water available for transport of solutes. The chemistry of the soil solution was more predictable, as it was governed mainly by nutrient uptake, cation exchange reactions and the seasonal wetting and drying cycles. The chemistry of the deep subsurface flow was often intermediate between that of the soil solution and that of the H-layer throughflow; this suggested a mixture of displaced pre-event soil solution and of H-layer throughflow circulating through preferential flow paths. With humid antecedent conditions, the chemistry of the deep subsurface flow approached that of the soil solution. The cation concentration relationships in the soil solution were strongly linear. In a homogeneous soil, cation exchange theory predicts this to be expected only for cations of the same charge, whereas cations of different charges should follow power relationships. Our results, however, are consistent with a theoretical approach involving cation exchange reactions in a highly heterogeneous environment. Indeed, our study illustrates the heterogeneous nature of the soils, as the power relationship has been obscured completely. Soilwater chemistries were markedly different from those of streamwater, particularly under dry conditions. During baseflow, the stream is fed by groundwater, and the soils are probably disconnected from the stream. During humid periods, the chemistry of the streamwater tends toward that of the deep subsurface flow. Chemical hydrograph separation indicates that, on average, stormflow water comprises an approximately one to one mixture of groundwater and deep subsurface flow.

EFFECTS OF IRRIGATION AND FERTILIZATION ON STEM DIAMETER GROWTH IN A MEDITERRANEAN HELM OAK FOREST (FOREST ECOLOGY AND MANAGEMENT, 1994)
The effects of irrigation and fertilization on stem diameter growth are reported for helm oak (Quercus ilex L.), an evergreen tree that is a common dominant in Mediterranean forests. The experiment was conducted at Prades (northeastern Spain) in a helm oak stand with a high density of stems of resprout origin (($) over bar x = 18275 stems ha(-1)), a widespread stand structure in the abandoned coppices that cover extensive tracts of Mediterranean mountains. Mean annual rainfall is 580 mm. Eight treatments were used in each of three blocks, resulting from the factorial combination of: (i) irrigation at rates of about 20 mm week(-1) during three consecutive warm seasons; (ii) nitrogen fertilization in a single application of 250 kg N ha(-1); (iii) phosphorus fertilization in a single application of 125 kg P ha(-1). Stem diameters at 50 cm from the ground were measured before and 3 years after treatment application began. Stem diameter increments in control plots were very low (($) over bar x+/-SE 0.27+/-0.07 mm year(-1)), probably as a result of the high stand density and low water availability. Stem diameter growth was positively but loosely correlated with initial stem diameter. Irrigation significantly (P<0.01) increased mean stem diameter growth by 66%, but N and P fertilization did not. Surprisingly, there were no significant interactions between irrigation and fertilization, i.e. irrigated and fertilized trees did not grow significantly faster than irrigated-only trees. Effects of irrigation were larger on plots having lower initial basal area of helm oak. Irrigation increased stem diameter growth more in large trees than in smaller ones, thus enhancing the pre-existent inequalities in growth rates. Stem diameter growth in this high density stand is limited by water availability but has not responded to N or P additions during the first 3 years after fertilization.

Growth response of holm oak (Quercus ilex L) to commercial thinning in the Montseny mountains (NE Spain) (Ann. For. Sci., 1993)
Growth responses of holm oak (Quercus ilex) to commercial thinning were studied in the Montseny Biosphere Reserve (northeast Spain), where selection thinning for firewood production is currently the dominant form of management in holm oak forests. Thinning significantly increased mean stem diameter increment by 83% over that of unthinned plots during the 6-9-yr period after thinning, and by 48% from 9-12 yr after thinning. Absolute diameter increment was positively correlated with initial diameter at 1.30 m from the ground (dbh) both in thinned and unthinned plots. Thinning increased growth in large trees more than in smaller trees. Relative diameter growth was negatively correlated with initial dbh. It is concluded that individual holm oak stems in previously coppiced stands respond vigourously to thinning, and still do so 6-9 yr after thinning. The growth response diminishes 9-12 yr after thinning due to canopy closure. However, absolute rates of stand growth, as well as basal area and stem biomass increments, were unaffected by thinning during these time intervals, an example of density compensation.

COMPARISON OF THE HYDROLOGICAL CHARACTERISTICS OF 3 SMALL EXPERIMENTAL HOLM OAK FORESTED CATCHMENTS IN NE SPAIN IN RELATION TO LARGER AREAS (VEGETATIO, 1992)
Precipitation and streamflow have been measured in three small (0.04-0.52 km2) experimental catchments covered by dense holm oak (Quercus ilex L.) forests. Two of them are in the Prades mountains and one in the Montseny mountains (NE Spain). Here we test the hydrological representativeness of these catchments against the streamflow record at two nearby larger (34-60 km2) catchments, one from each massif. Comparisons of (i) annual streamflow, (ii) seasonal distribution of streamflow, and (iii) flow duration curves were made. At Prades, for the period of common record, mean annual precipitation was about 580 mm, and mean annual streamflow 44-81 mm at the two experimental catchments and 102 mm at the larger one. Most streamflow occurred during winter and spring in the three catchments. At Montseny, rainfall was higher, and mean annual streamflow was 495 mm in the experimental catchment, and 760 mm in the larger catchment, though these data were obtained in different periods in each catchment. Streamflow was roughly equal in autumn, winter and spring. At both sites flow duration curves were fairly similar in the small experimental catchments and the larger catchments. The higher streamflow at Montseny is reflected in its flow duration curves being well above those at Prades. The experimental catchments at Prades are thus fairly representative of the investigated hydrological characteristics. At Montseny, hydrological differences between the experimental catchment and the larger catchment are probably due to the higher mean altitude of the latter and to the non-overlapping periods of their streamflow records.

Is primary production in holm oak forests nutrient limited? (Plant Ecology, 1992)
Correlations between primary production and patterns of nutrient use and nutrient availability were investigated in 18 plots in closed holm oak (Quercus ilex L.) stands in the Montseny mountains (NE Spain), searching for evidence of nutrient limitation on primary production. The plots spanned a range of altitudes and slope aspects within a catchment. Nutrients considered were nitrogen (N), phospho- rus (P), potassium (K) and magnesium (Mg) in plant samples, and the above plus calcium (Ca) and sodium (Na) in the soil. Primary production was found by summing the annual aboveground biomass increment to the annual litterfall. Across plots, primary production was correlated with the annual re- turn of nutrients in litterfall, but this relationship probably arose from the common effects of the amount of litterfall on both primary production and nutrient return, and not from any nutrient limitation. Pri- mary production was not significantly correlated with nutrient concentrations in mature leaves nor leaf litterfall, nor with absolute or relative foliar retranslocation of nutrients before leaf abscission, nor with the concentration and content (kg/ha) of total N, extractable P, and exchangeable K, Mg, Ca and Na in the upper mineral soil. We conclude that there is no correlational evidence that primary production is nutrient limited in this holm oak forest.